The Cefazolin Inoculum Effect Is Associated With Increased Mortality in Methicillin-Susceptible Staphylococcus aureus Bacteremia. (23rd May 2018) - Miller, William R; Seas, Carlos; Carvajal, Lina P; Diaz, Lorena; Echeverri, Aura M; Ferro, Carolina; Rios, Rafael; Porras, Paola; Luna, Carlos; Gotuzzo, Eduardo; Munita, Jose M; Nannini, Esteban; et al.
Abstract: Background: Recent studies have favored the use of cefazolin over nafcillin for the treatment of methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia. The clinical influence of the cefazolin inoculum effect (CzIE) in the effectiveness of cephalosporins for severe MSSA infections has not been evaluated. Methods: We prospectively included patients from 3 Argentinian hospitals with S. aureus bacteremia. Cefazolin minimum inhibitory concentrations (MICs) were determined at standard (10 5 colony-forming units [CFU]/mL) and high (10 7 CFU/mL) inoculum. The CzIE was defined as an increase of MIC to ≥16 µg/mL when tested at high inoculum. Whole-genome sequencing was performed in all isolates. Results: A total of 77 patients, contributing 89 MSSA isolates, were included in the study; 42 patients (54.5%) had isolates with the CzIE. In univariate analysis, patients with MSSA exhibiting the CzIE had increased 30-day mortality ( P = .034) and were more likely to have catheter-associated or unknown source of bacteremia ( P = .033) compared with patients infected with MSSA isolates without the CzIE. No statistically significant difference between the groups was observed in age, clinical illness severity, place of acquisition (community vs hospital), or presence of endocarditis. The CzIE remained associated with increased 30-day mortality in multivariate analysis (risk ratio, 2.65; 95% confidence interval, 1.10–6.42; P = .03). MSSA genomes displayed a high degree of heterogeneity, and the CzIE was not associated with a specific lineage. Conclusions: In patients with MSSA bacteremia where cephalosporins are used as firstline therapy, the CzIE was associated with increased 30-day mortality. Clinicians should be cautious when using cefazolin as firstline therapy for these infections.